Effects of blood flow restriction therapy in patients with knee osteoarthritis: protocol for an overview of systematic reviews - Machado, Felipe Alves; Almeida, Gustavo J.; do Vale, André Luiz Maia; Ribeiro, Alexandre Lima de Araújo; Cipriano, Graziella França Bernardelli; Cipriano Junior, Gerson; Martins, Wagner Rodrigues (Frontiers in Rehabilitation Sciences, 2024)
Background Osteoarthritis (OA) is the most common and prevalent musculoskeletal disease associated with population aging, negatively impacting function and quality of life. A consequence of knee OA is quadriceps muscle weakness. Musculoskeletal rehabilitation using low load exercises, associated with Blood Flow Restriction (BFR) may be a useful alternative to high load exercises when those cannot be tolerated. Several systematic reviews have reported inconclusive results due to discrepancies in study findings, heterogeneity of results, evaluated time points, and research questions explored. Objective To perform an overview of systematic reviews with meta-analyses, synthesizing the most recent evidence on the effects of muscle strength training with BFR for knee OA. Methodology Systematic reviews that include primary controlled and randomized clinical trials will be considered for inclusion. Articles will be considered only if they present a clear and reproducible methodological structure, and when they clearly demonstrate that a critical analysis of the evidence was carried out using instrumented analysis. Narrative reviews, other types of review, overviews of systematic reviews, and diagnostic, prognostic and economic evaluation studies will be excluded. Studies must include adults aged 40 years and older with a diagnosis of knee OA. Two authors will perform an electronic search with guidance from an experienced librarian. The following databases will be searched: PubMed via MEDLINE, Embase, CENTRAL (Cochrane Central Register of Controlled Trials), PEDro, Cumulative Index to Nursing and Allied Health Literature (CINAHL) via EBSCO host, Web of Science, and the gray literature. The search strategy used in the databases will follow the acronym PICOS (population, intervention, comparison, outcome, and study design). Screening (i.e., titles and abstracts) of studies identified by the search strategy will be selected using Rayyan (http://rayyan.qcri.org). The quality assessment will be performed using the “Assessment of Multiple Systematic Reviews” (AMSTAR-2) tool. Systematic Review Registration PROSPERO, CRD42022367209.